Autonomic Nervous System and Recall Modeling in Audiovisual Emotion-Mediated Advertising Using Partial Least Squares-Path Modeling - Barquero-Pérez, Óscar; Cámara-Vázquez, Miguel Angel; Vadillo-Valderrama, Alba; Goya-Esteban, Rebeca (Frontiers in Psychology, 2020)
Interest in improving advertisement impact on potential consumers has increased a lot recently. One well-known strategy is to use emotion-based advertisements to create an emotional link with consumers and enhance the memorization process. In recent years, the use of Neuromarketing techniques allowed us to obtain more objective information on this process. However, the role of the autonomic nervous systems in the memorization process using emotional advertisement still needs further investigation. In this work, we propose to use two physiological signals, namely, the electrocardiogram (heart rate variability, HRV) and the electrodermal activity (EDA) to obtain objective indices of the ANS. We measured these signals in 43 subjects during the observation of 6 different spots, each one conveying a different emotion (rational, disgust, anger, surprise and sadness). After observing the spots, the subjects were asked to answer a questionnaire to measure the spontaneous and induced recall. We propose to use a statistical data-driven model based on Partial Least Squares - Path Modeling (PSL-PM), which allows to incorporate context knowledge by defining a relational graph of unobservable variables (latent variables, LV), which in turn are estimated by the measured variable. We defined four LVs, namely, sympathetic and vagal, which are connected with the third LV, ANS, and finally, the fourth LV being a measure of the recall estimated from the questionnaire. The model is then fitted to the data. Results showed that the vagal activity (described by HRV indices) is the most important to describe the ANS activity, and they are inversely related, except for the clearly rational spot (without emotion). The model is able to explain, at most, 12% of the recall score of the subjects. This approach will allow to easily incorporate more physiological measurements, and provide with an easy to interpret model of the ANS response to emotional advertisements.